Negative Academic Emotion and Psychological Well-being in Chinese Rural-to-Urban Migrant Adolescents: Examining the Moderating Role of Cognitive Reappraisal - Wang, Daoyang; Li, Shuting; Hu, Mingming; Dong, Dan; Tao, Sha (Frontiers in Psychology, 2017)
The study aimed to explore the relationship among negative academic emotions (e.g., anxiety, shame, anger, boredom, hopelessness, disappointment, and hatred), psychological well-being (including life vitality, health concern, altruism commitment, self-value, friendly relationship, and personal development), and cognitive reappraisal in rural-to-urban migrant adolescents in China. Specifically, it was hypothesized that the relationship between psychological well-being and negative academic emotions is moderated by cognitive reappraisal. A total of 311 migrant adolescents aged 14–20 years were selected, including 132 boys and 179 girls. Results of a regression analysis showed that cognitive reappraisal (positive) and negative academic emotions were significant predictors of psychological well-being. The interaction effect between cognitive reappraisal and negative academic emotion was also a significant predictor of psychological well-being. In the simple slope analysis the group with a below average cognitive reappraisal score the negative academic emotions were associated with lower psychological well-being, whereas in the group with above average cognitive reappraisal the effect of negative academic emotions on psychological well-being was not significant. However, for those with a cognitive reappraisal score of 1 standard deviation above the average, the effect of negative academic emotions on psychological well-being was not significant. These results suggest that cognitive reappraisal was a significant moderator in the relationship between negative academic emotion and psychological well-being.